Kelas Sosial vs Pendapatan: Eksplorasi Faktor Penentu Pembelian Consumer Goods Dan Jasa - Triwijayati, Anna (Jurnal Ekonomi, 2018)
Social class and income influence consumer purchase behavior. This study aims to determine the relationship and difference between social class and income by purchasing consumer goods and services in Malang. This research used quantitative survey ex-post facto method. Research respondents were classified based on level of income and social class using the Index of Social Position (ISP). The quetionaire contaied 18 items of purchase, grouped into 5 types namely: food and drink, clothing, durable goods, investment, services and other products. Data analysis technique used chi-square. The results of the analysis show that the social class associate with the purchase of 17 items, while income associate with all items of goods and services consumed. Social class is more associated with fast food, clothes, electronic equipment, price and amount of investment and finance; income is more associated with meat, milk, the type of vehicle used, ownership of electronic tools, type of investment and finance, and housing and other buildings.